2019
DOI: 10.14744/scie.2019.05924
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome in patients with schizophrenia and bipolar disorders in community mental health center

Abstract: The aim of this study was to determine the frequency of metabolic syndrome (MetS) in patients with schizophrenia and bipolar disorder (BD) receiving antipsychotic (AP) medications. Methods: A total of 207 patients with schizophrenia and BD, diagnosed according to the DSM-IV criteria and receiving a regular AP treatment, were followed up in the Community Mental Health Center. The MetS was diagnosed according to the diagnostic criteria of the International Diabetes Federation. Patients with MetS were compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…There are consistent data in the literature on metabolic dysregulation in patients with schizophrenia. Although fewer studies have been conducted on BD patients on this subject, a study found that metabolic syndrome frequency was higher in bipolar patients compared to schizophrenia patients 7 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…There are consistent data in the literature on metabolic dysregulation in patients with schizophrenia. Although fewer studies have been conducted on BD patients on this subject, a study found that metabolic syndrome frequency was higher in bipolar patients compared to schizophrenia patients 7 .…”
Section: Discussionmentioning
confidence: 97%
“…The results of studies comparing bipolar and schizophrenic patients in terms of metabolic parameters differ. Besides there are many studies reporting worse metabolic results in patients with schizophrenia, there are also studies comparing the two diagnostic groups in this respect and demonstrating the metabolic parameters of patients with BD more negatively 7,14,17 . There are many factors that affect metabolic parameters in psychiatric diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation